The Middle East and Africa Code of Promotional Practices in the pharmaceutical industry - Sand Salhout; Clemens Bechter (Administrative Sciences, 2018)
The pharmaceutical industry is known for investing heavily in promotions targeted at healthcare professionals (HCPs). Governments around the world try to regulate unwanted promotional practices in different ways. Where binding laws are in place in the U.S.A., European governments favor self-regulation. The purpose of this research is the evaluation of the Middle East and Africa Code of Promotional Practices (MEACPP) as a preliminary draft and its implications. Our paper fills a research gap by looking into the perceptions of the parties involved, analyzing their interests, and predicting possible outcomes. We used a mixed-method approach. Interviews were conducted with pharmaceutical companies and associations; while a questionnaire was administered to HCPs. Our findings suggest that all parties are in favor of more transparency. However, when it comes to disclosing the received financial support, the HCPs are hesitant. An estimated 20% would be willing to fully disclose their received benefits, which is in line with their European colleagues. Multinational pharmaceutical companies follow their own in-house standards and fear being at a competitive disadvantage when local companies can promote their drugs without any strings attached. MEA pharmaceutical companies do not see the potential benefits of analyzing the publicly available data to identify key opinion leaders (KOLs). The limitation of our research is the fact that the MEACPP has not been implemented yet and survey results are therefore based on expectations rather than real events.
Keywords: 350; Middle East and Africa Code of Promotional Practices; pharmaceutical industry; transparency code; self-regulation